Value‐Based Care in Lung Cancer. (2nd June 2016) - Eaton, Keith D.; Jagels, Barbara; Martins, Renato G.
Abstract : Since the beginning of the 21st century, the treatment of lung cancer has changed dramatically. New treatments are improving survival outcomes for patients but have led to dramatic increases in cost. In a value‐based payment system, patients should have access to comprehensive outcome measurements, including survival rates, quality of life, and cost. High value in cancer care will optimize the outcomes that matter to patients relative to cost.